Motivations for shared services to employ green management practices / Emmarelda Maswesi Ahmad … [et al.] - Ahmad, Emmarelda Maswesi; Ahmad Noruddin, Nur Adura; Ismail, Rina Fadhilah; Ishak, Nur Ashikin; Ghani, Erlane K (Faculty of Accountancy, 2019)
There has been a persistent demand by numerous stakeholders for green business practices due to the increasing awareness of environmental issues in the last few years. Many conferences, seminars, and campaigns have been held in order to educate business operators on the green concept as well as the need to comprehend the prospects of going green. It is undeniable that green management practices may entail additional costs, however, industry players should acknowledge that green or also known as environmental management is able to provide useful information needed to improve performance that leads to sustainable development. This study examines the motivations for shared services centres (SSCs) to go green and to discover the relationships between the motivations and green management practices among SSCs. These motivations refer to environmental regulations, environmental voluntary reporting, environmental training, managerial perception and economic benefits of green management practices. Built on the stakeholder theory, data was collected by means of questionnaire survey. The findings exposed that SSCs’ green management practices are at a low level. Furthermore, environmental training and environmental voluntary reporting are found to be strong motivations for SSCs to employ green management practices.